Ketimpangan Distribusi Kartu Indonesia Pintar: Sebuah Kajian terhadap Akses dan Implementasi di Indonesia - Simanjuntak, Putri Natalia; S, Berlian Seladmai Yanti; Simangunsong, Michelle; Berlianti, Berlianti (AHKAM, 2024)
This study aims to examine the distribution inequality of the Indonesia Smart Card (KIP) Program as one of the Indonesian government's efforts to improve access to education for the poor and vulnerable poor. This program is expected to reduce school dropout rates and provide more equitable educational opportunities. However, its implementation still faces various obstacles, such as inaccurate targeting of recipients, delays in fund disbursement, lack of assistance, and the amount of assistance that is considered insufficient. This study uses a qualitative approach with in-depth interviews, observation, and document analysis to explore the factors that influence the success and failure of KIP distribution in various parts of Indonesia. The results show that while the program provides short-term benefits in easing the economic burden of recipient families, its impact on improving long-term economic independence is limited. This study recommends improvements in the data collection mechanism, beneficiary verification, and more intensive mentoring to ensure program effectiveness. Thus, it is expected that KIP can be more optimal in supporting education equity and poverty alleviation in Indonesia.